AN INVESTIGATION OF THE NEW HIGH-TC TL-V-SR-CA-CU-O AND TL-V-SR-CA-Y-CU-O SUPERCONDUCTORS - Liu, R; Zhou, W; Janes, R; Edwards, P (1991)
Superconductivity up to 105K has been achieved in the Tl-V-Sr-Ca-Cu-O and Tl-V-Sr-Ca-Y-Cu-O systems. The partial substitution of vanadium for thallium in the crystal lattice stabilizes the TlSr2CaCu2O7 phase and enhances superconductivity up to 80K. Importantly, 20% of Y 3+ replacement of Ca2+ sites in the (Tl,V)Sr 2CaCu2Oy compound reduces the excess hole concentration and increases superconductivity by about 20K.